Mediastinitis due to Gram‐negative bacteria is associated with increased mortality. (30th October 2013) - Charbonneau, H.; Maillet, J. M.; Faron, M.; Mangin, O.; Puymirat, E.; Le Besnerais, P.; Du Puy‐Montbrun, L.; Achouh, P.; Diehl, J. L.; Fagon, J.‐Y.; Mainardi, J.‐l.; Guerot, E.; et al.
Abstract The aim of this study was to describe the features of a large cohort of patients with postoperative mediastinitis, with particular regard to Gram‐negative bacteria (GNB), and assess their outcome. This bicentric retrospective cohort included all patients who were hospitalized in the Intensive Care Unit with mediastinitis after cardiac surgery during a 9‐year period. Three hundred and nine patients developed a mediastinitis with a mean age of 65 years and a mean standard Euroscore of six points. Ninety‐one patients (29.4%) developed a GNB mediastinitis (GNBm). Of the 364 pathogens involved, 103 GNB were identified. GNBm were more frequently polymicrobial (44% versus 3.2%; p <0.001). Being female was the sole independent risk factor of GNBm in multivariate analysis. Initial antimicrobial therapy was significantly more frequently inappropriate with GNBm compared with other microorganisms (24.6% versus 1.9%; p <0.001). Independent risk factors for inappropriateness of initial antimicrobial treatment were GNBm (OR = 8.58, 95%CI 2.53–29.02, p 0.0006), and polymicrobial mediastinitis (OR = 4.52, 95%CI 1.68–12.12, p 0.0028). GNBm were associated with more drainage failure, secondary infection, need for prolonged mechanical ventilation and/or use of vasopressors. Thirty‐day hospital mortality was significantly higher with GNBm (31.9 % versus 17.0%; p 0.004). GNBm was identified as an independent risk factor of hospital mortality (OR = 2.31, 95%CI 1.16–4.61, p 0.0179).